Studies of the Sorption of Palladium(II) Ions from Model Chloride Systems onto an Ion Exchanger Containing Isothiourea Groups and onto Weakly Basic Anion Exchangers of Various Types - Z. Hubicki; M. Leszczyńska (Adsorption Science & Technology)
The separation and determination of precious metals in minerals, alloys and environmental samples is very difficult due to their low concentration under natural circumstances. However, despite such difficulties, there has been a rapid development of chromatographic separation methods for noble metal ions. In the present work, laboratory studies of the selective removal of palladium(II) ions from 0.1–6.0 M HCl, 0.1–0.9 M HCl/0.9–0.1 M HNO 3 , 1.0 M AlCl 3 -0.1 M HCl and 1.0 M ZnCl 2 -0.1 M HCl onto various types of ion exchangers have been undertaken. In this context, the applicability of the selective ion exchanger Purolite S-920 and of the weakly basic anion exchangers Amberlyst A-21, Amberlite IRA-67 and Amberlite IRA-93 were examined. The sorption of Pd(II) ions was undertaken by both dynamic and static methods. The working ion-exchange capacities as well as the weight and bed distribution coefficients were calculated from the breakthrough curves for Pd(II) ions. The selective ion exchanger Purolite S-920 exhibited the highest value for the working ion-exchange capacity of Pd(II) ions.